Relations between starch fine molecular structures with gelatinization property under different moisture content. (15th February 2022) - Li, Enpeng; Cao, Panpan; Cao, Wei; Li, Cheng
Abstract: Although gelatinization property has been intensively investigated with its relation to starch structures, how a combination of starch molecular structures and moisture content affect the gelatinization remains unclear. The gelatinization of six rice starches with a wide range of amylose content was investigated under different moisture content in this study. Results showed that starch gelatinization temperatures increased and biphasic endothermic peaks appeared over the decreased moisture content. For the first time, amylose content was shown to have a parabolic relationship with gelatinization temperatures. Distinct linear relations among starch fine molecular structures with gelatinization parameters were observed under different moisture contents, which suggested that amylose short chains were involved in the first endothermic peak, while interactions among amylose intermediate chains and relatively shorter amylopectin trans-lamellar chains dominantly contributed to the second endothermic peak when gelatinized under limited moisture content. These results help in better understanding of starch structure-gelatinization relation. Graphical abstract: Critical starch structures and the possible mechanism in determining the biphasic endothermic peaks during the starch gelatinization under limited moisture content. Unlabelled Image